Proceedings of the Integrated Crop Management Conference 2016
DOI: 10.31274/icm-180809-195
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and increasing soybean yields

Abstract: • An understanding of the main factors influencing grain yield in soybean can provide key insights for making management decisions to increase yield. • Seed number is determined by the amount of photosynthate produced between R1 and R5 that is allocated to the seeds, divided by the minimum amount of photosynthate needed to keep a single seed from aborting. • Stresses or improvements in crop growth prior to flowering should not have a significant impact on final yield, provided that >95% light interception is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…A transcription factor identified in the region of the QTL CSp09 was found in Arabidopsis to be associated with ovule development ( Wei et al, 2015 ). A higher number of seeds per pod should result in higher grain yield as have been reported in soybean ( Van roekel and Purcell, 2016 ), peanut ( Songsri et al, 2009 ), and rapeseed ( Yang et al, 2016 ). Hence, the generally small seed size of the wild cowpea relatives notwithstanding, they are capable of contributing to higher grain yield in cultivated cowpea through an increase in the number of seeds in each pod, i.e., increasing the number of ovaries per pod.…”
Section: Exploring the Diversity And Potential Of Cwrs For Introgressmentioning
confidence: 61%
“…A transcription factor identified in the region of the QTL CSp09 was found in Arabidopsis to be associated with ovule development ( Wei et al, 2015 ). A higher number of seeds per pod should result in higher grain yield as have been reported in soybean ( Van roekel and Purcell, 2016 ), peanut ( Songsri et al, 2009 ), and rapeseed ( Yang et al, 2016 ). Hence, the generally small seed size of the wild cowpea relatives notwithstanding, they are capable of contributing to higher grain yield in cultivated cowpea through an increase in the number of seeds in each pod, i.e., increasing the number of ovaries per pod.…”
Section: Exploring the Diversity And Potential Of Cwrs For Introgressmentioning
confidence: 61%
“…Leaf chlorophyll content and leaf gas exchange intensity directly determine the photosynthetic characteristics of plants [43]. Photosynthetic characteristics of plants are mainly affected by changes in soil environment, moisture and nutrients [44]. Some studies have shown that biochar has the potential of improving the photosynthetic capacity of crop leaves [45,46].…”
Section: Effect Of Biochar On Chlorophyll Content and Gas Exchange Parameters Of Tomatomentioning
confidence: 99%
“…Moreover, the number of pods per plant seems to be the yield component that is most strongly affected by drought stress, which ultimately reduces the final seed yield depending on the duration and intensity of the stress period ( Shaw and Laing, 1966 ; Doss et al, 1974 ). By contrast, the number of seeds per pod and seed size appear to be more stable and genetically controlled yield components ( Shaw and Laing, 1966 ; Van Roekel and Purcell, 2016 ) which are relatively insensitive to drought stress conditions ( Momen et al, 1979 ).…”
Section: Introductionmentioning
confidence: 99%